2002
DOI: 10.1046/j.1523-1747.2002.19535.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanosome Morphologies in Murine Models of Hermansky–Pudlak Syndrome Reflect Blocks in Organelle Development

Abstract: Hermansky-Pudlak syndrome is an autosomal recessive disease characterized by pigment dilution and prolonged bleeding time. At least 15 mutant mouse strains have been classified as models of Hermansky-Pudlak syndrome. Some of the genes are implicated in intracellular vesicle trafficking: budding, targeting, and secretion. Many of the Hermansky-Pudlak syndrome genes remain uncharacterized and their functions are unknown. Clues to the functions of these genes can be found by analyzing the physiologic and cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
76
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 43 publications
15
76
2
Order By: Relevance
“…We found that mutations in DTNBP1/Dtnbp1 cause HPS-7/sdy, providing the first evidence to our knowledge that a mutation affecting a BLOC-1 complex component causes HPS in humans. The phenotypes of the four BLOC-1 mutants (pallid, muted, cappuccino and sandy) are the most severe of the mouse HPS mutants 6,22 , emphasizing the importance of BLOC-1 in the biogenesis of lysosome-related organelles, and their similar phenotypes 6,22 are consistent with their encoded proteins forming a common complex. One interpretation of the fact that dystrobrevin interacts with components (dysbindin and muted) of the BLOC-1 complex is that DPC components are involved in vesicle trafficking in nonmuscle tissues.…”
mentioning
confidence: 81%
“…We found that mutations in DTNBP1/Dtnbp1 cause HPS-7/sdy, providing the first evidence to our knowledge that a mutation affecting a BLOC-1 complex component causes HPS in humans. The phenotypes of the four BLOC-1 mutants (pallid, muted, cappuccino and sandy) are the most severe of the mouse HPS mutants 6,22 , emphasizing the importance of BLOC-1 in the biogenesis of lysosome-related organelles, and their similar phenotypes 6,22 are consistent with their encoded proteins forming a common complex. One interpretation of the fact that dystrobrevin interacts with components (dysbindin and muted) of the BLOC-1 complex is that DPC components are involved in vesicle trafficking in nonmuscle tissues.…”
mentioning
confidence: 81%
“…Samples were prepared (with minor modifications as noted in the SI Materials and Methods), and the percentage of melanosomes was determined as previously published (14). At least 10 individual melanoma cells were evaluated for each cell line or condition.…”
Section: Methodsmentioning
confidence: 99%
“…The Hps3 protein is part of a multimeric complex, BLOC-2, that regulates trafficking from the endosome; BLOC-2 also includes the subunit Hps5 and Hps6 proteins (22). We previously demonstrated that mutation of Hps3, Hps5, or Hps6 genes resulted in aberrant melanosome formation (14). To test if alteration of the function of BLOC-2 could influence chemosensitivity, we examined the effects of mutation of Hps6 on treatment sensitivity to cDDP.…”
Section: Chemosensitivity Is Up-regulated or Down-regulated By Receptmentioning
confidence: 99%
See 1 more Smart Citation
“…Cappuccino, pallidin, and dysbindin were originally identified as proteins that cause a severe pigmentation defect in mice when mutated 12,13 . These three proteins are components of the biogenesis of lysosome-related organelles complex 1 (BLOC-1), required for the proper sorting of cargo (such as TYRP1) from early endosomes to lysosome-related organelles 14 .…”
Section: Introductionmentioning
confidence: 99%